DIGITAL COMPETENCY IN HIGHER EDUCATION: A -TEN YEAR BIBLIOMETRIC ANALYSIS OF RESEARCH TRENDS, KEY CONTRIBUTORS, AND INFLUENTIAL PUBLICATIONS - Ibrahim, Siti Fairuz; Jamiat, Nurullizam; Anuar, Azyyati; Shawalludin, Syahrini; Abdul Rabu, Siti Nazleen (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study presents a bibliometric analysis of research on digital competency in higher education, based on Scopus-indexed publications from 2014 to 2024. This study reports the results using standard bibliometric indicators, which include (1) the current development and publication trends, (2) the most productive contributors in terms of authors, institutions, countries, and source titles, and (3) the most highly cited documents in the field. The data were analyzed using BiblioMagika® and VOSviewer, which facilitated the construction and visualization of bibliometric networks. The findings offer valuable insights into the evolving landscape of digital competency in higher education, highlighting key trends, influential contributors, and areas for future exploration.